2009
DOI: 10.1158/1078-0432.ccr-09-0886
|View full text |Cite
|
Sign up to set email alerts
|

Differential Clinical Significance of Individual NKG2D Ligands in Melanoma: Soluble ULBP2 as an Indicator of Poor Prognosis Superior to S100B

Abstract: Purpose: Cytotoxic lymphocytes interact with human tumor cells via the activating immunoreceptor NKG2D, recognizing a variety of stress-associated MIC and ULBP surface molecules. However, tumors can escape from this immunosurveillance by shedding NKG2D ligands (NKG2DL), rendering the soluble products detectable in patients' sera. Experimental Design: To elucidate the clinical significance of NKG2DL diversity, we studied their expression on melanoma tissues and their presence as soluble molecules in sera from >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(164 citation statements)
references
References 50 publications
7
150
1
4
Order By: Relevance
“…Identification of additional models insensitive to pan-HER inhibitors such as AZD8931, yet sensitive to MEDI3622, should prove to be fertile grounds for these efforts in conjunction with proteomic studies to identify novel ADAM17 substrates in these models. It is noteworthy that ligands which are immunosuppressive upon shedding, such as ULBP2 (39) and MICA (40), were among the proteomics hits in the OE21 model (Table 3) and H358 lung cancer cells (Supplementary Table S3). MEDI3622-mediated inhibition of circulating levels of these ligands has the potential to restore CD8 þ T-cell and NK cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of additional models insensitive to pan-HER inhibitors such as AZD8931, yet sensitive to MEDI3622, should prove to be fertile grounds for these efforts in conjunction with proteomic studies to identify novel ADAM17 substrates in these models. It is noteworthy that ligands which are immunosuppressive upon shedding, such as ULBP2 (39) and MICA (40), were among the proteomics hits in the OE21 model (Table 3) and H358 lung cancer cells (Supplementary Table S3). MEDI3622-mediated inhibition of circulating levels of these ligands has the potential to restore CD8 þ T-cell and NK cell function.…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, sULBP2 was associated as an indicator of poor prognosis superior to sMICA. 42 The functional consequences of increased sULBP2, however, remain speculative. It is reported that tumor-derived sMIC ligands impair the NKG2D receptor expression on T and NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works have shown the remarkable role of ULBP2 as a marker for disease progression [8,21]. In addition, it has been reported that proteasome inhibitor treatment leads to a higher sensitivity to NK-cell-mediated killing by upregulation of ULBP2 expression [22], supporting its potential relevance in the development of anticancer therapy.…”
Section: Nkg2d and Nkg2a Ligation Rescues Impaired Migrationmentioning
confidence: 97%
“…This effect was abrogated by costimulation of the NKG2A receptor, while the activation of this receptor alone did not affect cell migration. These results are in keeping with the study of Culley et al [20], which describes that activating signals in NK cells, such as interaction of NKG2D with MICA promotes a stop signal to form the IS, while inhibitory signals may reverse this effect.Recent works have shown the remarkable role of ULBP2 as a marker for disease progression [8,21]. In addition, it has been reported that proteasome inhibitor treatment leads to a higher sensitivity to NK-cell-mediated killing by upregulation of ULBP2 expression [22], supporting its potential relevance in the development of anticancer therapy.…”
mentioning
confidence: 97%